BS EN IEC 61753-043-2. Fibre optic interconnecting devices and passive components. Performance standard. Part 043-02. Simplex patch-cord style single-mode fibre wavelength selective devices with cylindrical ferrule connectors for category C. Controlled environment (4th June 2021) - British Standards Institution,
No abstract available